Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By blending fluorine phosphorus compounds into the positive electrode active material of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, the problem of unstable body phase structure of the positive electrode material under high temperature and high pressure is solved, and the stability and storage performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202410233268.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-02-29
AI Technical Summary
The body phase structure of the positive electrode material under high temperature and high pressure is unstable, resulting in a shortening of the life of lithium-ion batteries, limiting its industrial applications.
The fluorine phosphorus compound is blended into the positive electrode active host material of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide. The fluorine phosphorus compound is located on the surface of the positive electrode active host material, inhibiting oxidation activity and stabilizing the body phase structure.
Enhance the stability of the cathode material in high temperature environments, improve the storage performance of the battery and reduce gas production problems, and extend the service life of the battery.
Smart Images

Figure BDA0004722300490000161 
Figure BDA0004722300490000171 
Figure HDA0004722300890000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are the most widely used electrochemical energy storage devices in the energy field. As the main material with the largest proportion in lithium-ion batteries, positive electrode materials have a great impact on the overall performance of the battery. However, the side reactions of positive electrode materials are intense under high temperature and high pressure, which shortens the life of the battery. Therefore, the industrialization of lithium-ion batteries under high temperature and high pressure is greatly limited. Summary of the invention
[0003] In view of this, the main technical problem to be solved by the present application is the instability of the bulk structure of the positive electrode material under high temperature and high pressure, thereby providing a positive electrode active material and its preparation method, a positive electrode plate, a battery and an electrical equipment, which can stabilize the bulk structure of the positive electrode material and enhance the stability of the positive electrode material under high temperature and high pressure conditions.
[0004] The first aspect of the present application provides a positive electrode active material. The positive electrode active material includes a positive electrode active main material and a fluorine phosphorus compound. The positive electrode active main material includes lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide; the fluorine phosphorus compound is mixed in the positive electrode active main material.
[0005] In the technical solution of the embodiment of the present application, the fluorine-phosphorus compound is mixed into the positive electrode active main material formed by lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide, which can inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature environment, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the fluorine-phosphorus compound is acidic and can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process, which leads to battery deterioration.
[0006] In any embodiment, the fluorophosphorus compound is located on the surface layer of the positive electrode active host material.
[0007] In the technical solution of the embodiment of the present application, the fluorine phosphorus compound located on the surface of the positive electrode active main material can inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature environment, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the fluorine phosphorus compound is acidic and can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process, which leads to battery deterioration.
[0008] In any embodiment, the fluorophosphorus compound comprises a structural formula of Li p P q O r F 2 A compound wherein 0.8≤p≤1.2, 0.8≤q≤1.2, and 1.8≤r≤2.2.
[0009] In the technical solution of the embodiment of the present application, the structural formula is Li p P q O r F 2 The fluorinated phosphorus compounds can enhance the stability of the overall structure of the positive electrode active material and maintain good electrical properties even at a high voltage of 4.5V.
[0010] In any embodiment, the cathode active host material comprises a structure of Li(Ni x Co y M z ) 1-u T u O 2 material, wherein M includes Mn or Al, T includes one or more of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al, x+y+z=1, 0.3≤x≤0.9, 0.03≤y≤0.3, 0.05≤z≤0.4, 0.0003≤u≤0.004.
[0011] In the technical solution of the embodiment of the present application, the structural formula is Li(Ni x Co y M z ) 1-u T u O 2 The positive electrode active main material has a hexagonal crystal structure, which has a higher energy density, that is, it has better energy storage performance under the same volume and mass; at the same time, it has higher chemical stability and is not prone to thermal runaway, so it has a longer service life.
[0012] In any embodiment, the positive electrode active host material is doped with fluorine and phosphorus.
[0013] In the technical solution of the embodiment of the present application, fluorine and phosphorus are doped in the positive electrode active main material formed by lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide. The fluorine element will be doped into the oxygen site of the hexagonal crystal system of the positive electrode active main material, and the phosphorus element will be doped into the hexagonal crystal lattice or / and the oxygen site of the hexagonal crystal system of the positive electrode active main material, so as to achieve the modification of the positive electrode active main material, inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature conditions, thereby significantly improving the storage performance of the battery and gas production problems.
[0014] In any embodiment, the fluorine phosphorus compound accounts for 0.015% to 0.4% of the total mass of the positive electrode active material. Optionally, the fluorine phosphorus compound accounts for 0.03% to 0.3% of the total mass of the positive electrode active material. By controlling the content of the fluorine phosphorus compound in the positive electrode active material, the residual alkali on the surface of the positive electrode active main material can be suppressed, and the stability of the positive electrode active material can be improved, so that the battery has excellent electrical properties.
[0015] In any embodiment, the volume average particle size DV50 of the positive electrode active material is 3 μm to 15 μm. By controlling the volume average particle size of the positive electrode active material to be 3 μm to 15 μm, the sites for lithium insertion and removal of the positive electrode active material are larger, ensuring better power performance of the battery.
[0016] The volume average particle size DV50 of the positive electrode active material is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0017] The second aspect of the present application also provides a method for preparing a positive electrode active material, which comprises: spraying a difluorophosphate solution on a nickel-cobalt metal precursor so that the difluorophosphate is coated on the nickel-cobalt metal precursor, wherein the nickel-cobalt metal precursor comprises a nickel-cobalt-manganese precursor or a nickel-cobalt-aluminum precursor; mixing the nickel-cobalt metal precursor coated with the difluorophosphate and a lithium source, and sintering them to form a lithium nickel-cobalt-manganese oxide or a lithium nickel-cobalt-aluminum oxide mixed with a fluorine-phosphorus compound.
[0018] In the technical solution of the embodiment of the present application, the difluorophosphate solution is coated on the surface of the nickel-cobalt metal precursor in the form of a spray, so that the contact between the difluorophosphate and the nickel-cobalt metal precursor is more uniform, which can reduce the occurrence of agglomeration of the difluorophosphate, and make the surface distribution of the lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide mixed with fluorophosphorus compounds finally formed more uniform and the difference in all directions is small.
[0019] In any embodiment, the spray coating time is 5 min to 60 min. Optionally, the spray coating time is 8 min to 30 min. Controlling the spray coating time within this time range is conducive to more uniform and sufficient mixing of the difluorophosphate solution and the nickel-cobalt metal precursor.
[0020] In any embodiment, the mass ratio of the difluorophosphate to the nickel-cobalt metal precursor in the difluorophosphate solution is 3×10 -4 ~4×10 -3 : 1. By controlling the mass ratio of difluorophosphate to nickel-cobalt metal precursor, the residual alkali on the surface of the positive electrode active main material can be suppressed, and the stability of the positive electrode active material can be improved, so that the battery has excellent electrical properties.
[0021] In any embodiment, a nickel-cobalt metal precursor coated with difluorophosphate and a lithium source are mixed, including: mixing a nickel-cobalt metal precursor coated with difluorophosphate, a lithium source and a metal doping source, wherein the metal doping source includes one or more metal oxides of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al.
[0022] In any embodiment, the nickel-cobalt metal precursor comprises a structural formula of (Ni a Co b M c ) d (OH) 2 , 0.3≤a≤0.9, 0.01≤b≤0.4, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, M includes Mn or Al. The hydroxide precursor is used as a material for preparing a positive electrode active material, so that the prepared positive electrode active material has the advantage of high specific capacity, good compatibility with the electrolyte, and wide application.
[0023] In any embodiment, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium acetate and lithium phosphate. The lithium source is used to provide lithium element, which has high electrochemical activity and can react chemically with other elements in the battery to release electrons and generate current.
[0024] In any embodiment, the mixing speed is 600 rpm to 2000 rpm, and the mixing time is 30 min to 300 min. This mixing method allows the nickel-cobalt metal precursor and the lithium source to be mixed more fully.
[0025] In any embodiment, the sintering temperature is 900°C to 950°C, and the sintering time is 10h to 33h. In the embodiment of the present application, the sintering temperature and sintering time are controlled to control the synthesis of nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, and the volume average particle size DV50 of the nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide is within a preset range, for example, within a range of 3μm to 15μm, so that the power performance of the battery is better.
[0026] The third aspect of the present application also provides a positive electrode sheet, including the positive electrode active material of the first aspect of the present application, and / or the positive electrode active material prepared by the preparation method of the positive electrode active material of the second aspect of the present application. Since the positive electrode sheet of the present application includes the positive electrode active material provided by the present application, it has at least the same advantages as the positive electrode active material.
[0027] The fourth aspect of the present application also provides a battery, including the positive electrode active material of the first aspect of the present application, and / or the positive electrode active material prepared by the method for preparing the positive electrode active material of the second aspect of the present application, or the positive electrode sheet of the third aspect of the present application. Since the battery of the present application includes the positive electrode active material provided by the present application, it has at least the same advantages as the positive electrode active material.
[0028] The fifth aspect of the present application further provides an electrical device, comprising the battery of the fourth aspect of the present application. Since the electrical device of the present application comprises the battery provided by the present application, it has at least the same advantages as the battery.
[0029] The beneficial effects of the present application are as follows: Different from the prior art, the positive electrode active material of the present application includes a positive electrode active main material and a fluorophosphorus compound, and the fluorophosphorus compound is mixed in the positive electrode active main material. The fluorophosphorus compound can achieve the modification of the positive electrode active main material, inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature environment, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the fluorophosphorus compound can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process and cause the battery to deteriorate.
[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic structural diagram of a battery cell according to one embodiment of the present application.
[0032] Figure 2 It is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application.
[0033] Figure 3a It is a schematic diagram of the partial structure of an electrical equipment according to one embodiment of the present application.
[0034] Figure 3b It is a schematic diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION
[0035] Below, the battery cells, batteries and electrical equipment of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0036] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0041] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] As the main material with the largest proportion in lithium-ion batteries, positive electrode active materials have a great influence on the overall performance of the battery. In order to maximize the energy performance of ternary positive electrode active materials and minimize the cost in current technology, the voltage used is often increased. However, the side reactions of positive electrode active materials are intense under high voltage (3.7V~4.5V), which shortens their lifespan. Therefore, the industrialization of high-voltage ternary positive electrode active materials is greatly limited. The conventional modification method of high-voltage ternary positive electrode active materials is mainly aimed at the surface of positive electrode active materials. The modified materials are coated on the surface of positive electrode active materials to inhibit the side reactions between the surface of positive electrode active materials and electrolytes. However, the surface polarization of positive electrode active materials coated with modified materials is too large, resulting in poor battery capacity. In addition, the surface coating layer hinders the channel for lithium ion transmission, causing serious gram capacity decay and serious battery cycle decay. On the other hand, the surface coating layer has poor side reaction inhibition effect under high temperature and high pressure.
[0043] Based on this, the present application proposes a positive electrode active material. The positive electrode active material includes a positive electrode active main material and a fluorine phosphorus compound. The positive electrode active main material includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide; the fluorine phosphorus compound is mixed in the positive electrode active main material.
[0044] In the embodiment of the present application, the fluorine-phosphorus compound is mixed into the positive electrode active main material formed by lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide, which can inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature environment, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the fluorine-phosphorus compound is acidic and can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process, which leads to battery deterioration.
[0045] In some embodiments of the present application, the fluorine phosphorus compound is located on the surface layer of the positive electrode active host material.
[0046] In the technical solution of the embodiment of the present application, the fluorine phosphorus compound located on the surface of the positive electrode active main material can inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature environment, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the fluorine phosphorus compound is acidic and can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process, which leads to battery deterioration.
[0047] In some embodiments of the present application, the fluorophosphorus compound includes a structural formula of Li p P q O r F 2 A compound wherein 0.8≤p≤1.2, 0.8≤q≤1.2, 1.8≤r≤2.2. The structural formula is Li p P q O r F 2 Fluorophosphorus compounds can enhance the stability of the structure of the positive electrode active material and maintain good electrical performance even at a high voltage of 4.5 V. At the same time, fluorine phosphorus compounds are acidic and can react with residual alkali on the surface of the positive electrode active main material to reduce the decomposition of residual alkali during the battery charging and discharging process, which may lead to battery deterioration.
[0048] In some embodiments of the present application, the cathode active host material includes a structural formula of Li(Ni x Co y M z ) 1-u T u O 2material, wherein M includes Mn or Al, T includes one or more of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al, x+y+z+u=1, 0.3≤x≤0.9, 0.03≤y≤0.3, 0.05≤z≤0.4, 0.0003≤u≤0.004.
[0049] In the technical solution of the embodiment of the present application, the structural formula is Li(Ni x Co y M z ) 1-u T u O 2 The positive electrode active main material has a hexagonal crystal structure, which has a higher energy density, that is, it has better energy storage performance under the same volume and mass; at the same time, it has higher chemical stability and is not prone to thermal runaway, so it has a longer service life.
[0050] In some embodiments of the present application, the positive electrode active host material is doped with fluorine and phosphorus.
[0051] In the technical solution of the embodiment of the present application, fluorine and phosphorus are doped in the positive electrode active main material formed by lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide. The fluorine element will be doped into the oxygen site of the hexagonal crystal system of the positive electrode active main material, and the phosphorus element will be doped into the hexagonal crystal lattice or / and the oxygen site of the hexagonal crystal system of the positive electrode active main material, so as to achieve the modification of the positive electrode active main material, inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature conditions, thereby significantly improving the storage performance of the battery and gas production problems.
[0052] In some embodiments of the present application, the fluorine phosphorus compound accounts for 0.015% to 0.4% of the total mass of the positive electrode active material, and optionally 0.03% to 0.3%. For example, it can be 0.015%, 0.03%, 0.059%, 0.15%, 0.19%, 0.26%, 0.29%, 0.3%, 0.34%, 0.4%, etc., or a range consisting of any two of the above values, for example, 0.015% to 0.26%, 0.26% to 0.34%, 0.34% to 0.4%, etc. By controlling the content of the fluorine phosphorus compound in the positive electrode active material, the residual alkali on the surface of the positive electrode active main material can be suppressed, and the stability of the positive electrode active material can be improved, so that the battery has excellent electrical properties.
[0053] In some embodiments of the present application, the volume average particle size DV50 of the positive electrode active material is 3μm to 15μm. By controlling the volume average particle size of the positive electrode active material to be 3μm to 15μm, the sites for lithium insertion and removal of the positive electrode active material are larger, ensuring better power performance of the battery cell. Among them, the volume average particle size DV50 of the positive electrode active material can be 3μm, 4.2μm, 5.5μm, 6.9μm, 9.4μm, 12.5μm, 15μm, etc., or a range consisting of any two of the above values, for example, 3μm to 6.9μm, 6.9μm to 12.5μm, 12.5μm to 15μm, etc. Among them, the volume average particle size DV50 of the positive electrode active material is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0054] The second technical solution adopted in the present application is: to provide a method for preparing a positive electrode active material, the method comprising: spraying a difluorophosphate solution on a nickel-cobalt metal precursor so that the difluorophosphate is coated on the nickel-cobalt metal precursor, wherein the nickel-cobalt metal precursor comprises a nickel-cobalt-manganese precursor or a nickel-cobalt-aluminum precursor; mixing the nickel-cobalt metal precursor coated with the difluorophosphate and a lithium source, sintering, and forming a lithium nickel-cobalt-manganese oxide or a lithium nickel-cobalt-aluminum oxide mixed with a fluorine-phosphorus compound.
[0055] Specifically, the method for preparing the positive electrode active material comprises the following steps:
[0056] Step 1: Fully dissolve lithium difluorophosphate in deionized water to form a difluorophosphate solution, and coat the difluorophosphate solution on the nickel-cobalt-manganese precursor or the nickel-cobalt-aluminum precursor by wet spraying.
[0057] Lithium difluorophosphate is easily soluble in water. In this embodiment, harmless and pollution-free deionized water is preferably used as a solvent to dissolve lithium difluorophosphate in deionized water to form a difluorophosphate solution. After the solution is formed, it can be coated in a spraying manner. Of course, in other embodiments, lithium difluorophosphate can also be dissolved in an alcohol solvent such as methanol or ethanol.
[0058] In this embodiment, the mass ratio of the difluorophosphate to the nickel-cobalt metal precursor in the difluorophosphate solution is 3×10 -4 ~4×10 -3 :1. By controlling the mass ratio of difluorophosphate to nickel-cobalt metal precursor, the residual alkali on the surface of the positive electrode active main material can be suppressed, and the stability of the positive electrode active material can be improved, so that the battery has excellent electrical properties. Among them, the mass ratio of difluorophosphate to nickel-cobalt metal precursor in the difluorophosphate solution can be 3.0×10 -4 :1,3.1×10 -4 :1,4.1×10 -4:1,5.5×10 -4 :1,2.1×10 -3 :1,3.8×10 -3 :1,4×10 -3 :1, etc., or a range consisting of any two of the above values, for example, 3.0×10 -4 :1~5.5×10 -4 :1,5.5×10 -4 :1~2.1×10 -3 :1,2.1×10 -3 :1~4×10 -3 :1, etc.
[0059] Then, the difluorophosphate solution is coated on the surface of the nickel-cobalt-manganese precursor or the nickel-cobalt-aluminum precursor by spray coating. The spraying method can make the lithium difluorophosphate solution and the nickel-cobalt metal precursor fully mixed to achieve uniform coating, which can reduce the occurrence of difluorophosphate agglomeration, so that when sintering in a high-temperature environment later, the effect of lithium difluorophosphate can be better exerted, the positive electrode active main material can be modified, the oxidation activity of the positive electrode active main material can be suppressed, and the bulk structure of the positive electrode active main material can be stabilized, so that the stability of the positive electrode active material in a high-temperature environment is enhanced.
[0060] In this embodiment, the spray coating spray time is 5min to 60min, and optionally, the spray time is 8min to 30min. Controlling the spray coating time within this time range is conducive to more uniform and sufficient mixing of the difluorophosphate solution and the nickel-cobalt metal precursor. The spray time can be 5min, 8min, 15min, 26min, 30min, 37min, 45min, 58min, 60min, etc., or a range consisting of any two of the above values, for example, 5min to 26min, 26min to 45min, 45min to 60min, etc.
[0061] Step 2: Mix the nickel-cobalt metal precursor coated with difluorophosphate and a lithium source, and sinter them to form lithium nickel-cobalt-manganese oxide or lithium nickel-cobalt-aluminum oxide mixed with fluorine-phosphorus compounds.
[0062] Specifically, the step includes: mixing a nickel-cobalt metal precursor coated with difluorophosphate, a lithium source and a metal doping source. The present embodiment does not limit the mixing order. The nickel-cobalt metal precursor coated with difluorophosphate may be mixed with a lithium source first and then with a metal doping source, or the nickel-cobalt metal precursor coated with difluorophosphate may be mixed with a metal doping source first and then with a lithium source, or the nickel-cobalt metal precursor coated with difluorophosphate may be mixed with a lithium source and a metal doping source at the same time. The metal doping source includes one or more metal oxides of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al. In the embodiment of the present application, lithium nickel-cobalt-manganese oxide mixed with fluorine-phosphorus compounds and lithium nickel-cobalt-aluminum oxide mixed with fluorine-phosphorus compounds may be prepared by further sintering.
[0063] In some embodiments of the present application, the nickel-cobalt metal precursor includes a structural formula of (Ni a Co b M c ) d (OH) 2 , 0.3≤a≤0.9, 0.01≤b≤0.4, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, M includes Mn or Al. The hydroxide precursor is used as a material for preparing positive electrode active materials, which has the advantage of high specific capacity, good compatibility with electrolyte, and wide application.
[0064] The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium acetate and lithium phosphate. The lithium source is used to provide lithium elements. Lithium elements have high electrochemical activity and can react chemically with other elements in the battery to release electrons and generate current.
[0065] In some embodiments of the present application, the nickel-cobalt metal precursor may include but is not limited to (Ni 0.3 Co 0.4 Mn 0.3 ) 0.95 (OH) 2 、(Ni 0.4 Co 0.2 Mn 0.4 ) 0.96 (OH) 2 、(Ni 0.6 Co 0.1 Mn 0.3 ) 0.97 (OH) 2 、(Ni 0.7 Co 0.05 Al 0.25 ) 0.98 (OH) 2 and(Ni0.9 Co 0.01 Al 0.09 ) 1 (OH) 2 At least one of .
[0066] The nickel-cobalt metal precursor coated with difluorophosphate, the lithium source and the metal doping source are mixed in an inclined roller mill and a high-speed mixer at a mixing speed of 600 rpm to 2000 rpm for a mixing time of 30 min to 300 min. This mixing method allows the nickel-cobalt metal precursor and the lithium source to be mixed more fully. The mixing speed can be 600rpm, 780rpm, 890rpm, 1350rpm, 1590rpm, 1780rpm, 1950rpm, 2000rpm, etc., or a range consisting of any two of the above values, for example, 600rpm-890rpm, 890rpm-1590rpm, 1590rpm-2000rpm, etc.; the mixing time can be 30min, 65min, 95min, 156min, 210min, 260min, 300min, etc., or a range consisting of any two of the above values, for example, 30min-95min, 95min-210min, 210min-300min, etc.
[0067] After mixing, sintering is performed at a temperature of 900°C to 950°C and a sintering time of 10h to 33h. The related art uses low-temperature coating technology, and the temperature of low-temperature sintering is 400°C to 500°C. Low-temperature sintering can usually only coat lithium difluorophosphate on the outer surface of the positive electrode active material, and cannot be mixed into the interior of the positive electrode active material. At the same time, lithium difluorophosphate is not completely decomposed, and harmful substances such as hydrogen fluoride that are not completely burned are produced. The sintering temperature of this embodiment is 900°C to 950°C, while the decomposition temperature of fluorine-phosphorus compounds is relatively low, less than 300°C, so in fact, lithium difluorophosphate has been decomposed at more than 300 degrees Celsius. When the temperature is raised to 900°C to 950°C, lithium difluorophosphate will decompose fluorine and phosphorus elements, and the fluorine and phosphorus elements will migrate into the interior of the positive electrode active material to be doped in the bulk phase of the positive electrode active main material. Among them, the F element will be doped in the oxygen site of the hexagonal crystal system of the positive electrode active main material, and the P element will be doped in the hexagonal crystal lattice or / and the oxygen site of the hexagonal crystal system of the positive electrode active main material, so as to achieve the modification of the positive electrode active main material, inhibit the oxidation activity of the positive electrode active main material, stabilize the bulk structure of the positive electrode active main material, and enhance the stability of the positive electrode active material under high temperature conditions, thereby significantly improving the storage performance and gas production problems of the battery. The embodiment of the present application controls the sintering temperature within the range of 900°C to 950°C and the sintering time within the range of 10h to 33h, so as to control the synthesis of nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide, and make the volume average particle size DV50 of nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide within a preset range, for example, within the range of 3μm to 15μm, so that the power performance of the battery is better. The sintering temperature can be 900°C, 910°C, 925°C, 934°C, 945°C, 950°C, etc., or a range composed of any two of the above values, such as 900°C to 925°C, 925°C to 934°C, 934°C to 950°C, etc.; the sintering time can be 10h, 15h, 20h, 25h, 30h, 33h, etc., or a range composed of any two of the above values, such as 10h to 15h, 15h to 25h, 25h to 33h, etc.
[0068] It should be noted that in the process of making the positive active material, after sintering at 900°C to 950°C, the fluorine-phosphorus compound in the positive active material will decompose F and P elements, and the F and P elements will be doped into lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide (i.e., the bulk phase of the positive active main material). After sintering, after cooling, on the one hand, some F and P elements are still doped in lithium nickel cobalt manganese oxide or / and lithium nickel cobalt aluminum oxide. The F element will be doped in the oxygen position of the hexagonal system of the positive active main material, and the P element will be doped between the lattices of the hexagonal system of the positive active main material and / or doped in the oxygen position of the hexagonal system. The doping is to stabilize the bulk structure of the positive active main material and improve the structural stability. Among them, the F element and the P element doped in the positive active main material can be characterized by XRD refinement, observing the shift of the characteristic peak of the oxygen position or the change of other characteristic peaks. On the second hand, after sintering, after cooling, at least part of the decomposed F and P elements will re-form fluorine-phosphorus compounds. Therefore, after the final sintering is completed, the positive electrode active material will show fluorine-phosphorus compounds, and the re-formed fluorine-phosphorus compounds are located on the surface of the positive electrode active main material, which can stabilize the interface and improve the stability of the positive electrode active main material. It should be noted that the re-formed fluorine-phosphorus compounds cannot decompose the F element and the P element.
[0069] The positive electrode active material prepared by the above preparation process contains difluorophosphate. Under high temperature conditions greater than 300°C, i.e., 900°C to 950°C, the difluorophosphate will decompose F elements and P elements to be doped into the bulk phase of the positive electrode active main material, thereby modifying the positive electrode active main material, inhibiting the oxidation activity of the positive electrode active main material, and stabilizing the bulk structure of the positive electrode active main material, so that the stability of the positive electrode active material is enhanced under high temperature conditions, thereby significantly improving the storage performance and gas production problems of the battery. In addition, the difluorophosphate on the surface of the positive electrode active material is acidic and can also react with the residual alkali on the surface of the positive electrode active main material to reduce the decomposition of the residual alkali during the battery charging and discharging process, which leads to battery deterioration. The positive electrode active material prepared by the above preparation process has an excellent high-temperature storage life.
[0070] The third technical solution adopted by the present application is: to provide a positive electrode plate, including the positive electrode active material of the first aspect of the present application, and / or the positive electrode active material prepared by the preparation method of the positive electrode active material of the second aspect of the present application. Since the positive electrode plate of the present application includes the positive electrode active material provided by the present application, it has at least the same advantages as the positive electrode active material.
[0071] In addition, the battery cell, battery, and electric equipment of the present application will be described below with reference to the drawings as appropriate.
[0072] In the embodiments of the present application, a battery cell refers to the smallest unit that makes up a battery. A battery cell also includes an electrolyte and a separator. The separator is disposed between the positive electrode and the negative electrode, and mainly serves to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. During the battery charging and discharging process, the active ions Li + The electrolyte is embedded and released back and forth between the positive electrode and the negative electrode, and plays the role of conducting ions between the positive electrode and the negative electrode.
[0073] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the above embodiment of the present application.
[0074] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0075] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0076] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0077] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0078] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0079] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0080] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0081] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0082] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0083] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0084] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).
[0085] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0086] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0087] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.
[0088] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0089] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0090] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0091] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0092] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0093] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.
[0094] In some embodiments, Figure 1 As shown, the battery cell 10 may include an outer package. The outer package can be used to encapsulate the above-mentioned battery cell assembly 11 and electrolyte. The outer package includes an end cap 12, a shell 13 and other functional components.
[0095] The end cap 12 refers to a component that covers the opening of the shell 13 to isolate the internal environment of the battery cell 10 from the external environment. Without limitation, the shape of the end cap 12 can be adapted to the shape of the shell 13 to match the shell 13. Optionally, the end cap 12 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 12 is not easily deformed when squeezed and collided, so that the battery cell 10 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 12a can be provided on the end cap 12. The electrode terminal 12a can be used to electrically connect to the battery cell assembly 11 for outputting or inputting electrical energy of the battery cell 10. In some embodiments, the end cap 12 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 10 reaches a threshold. The material of the end cap 12 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member (not shown) may be provided inside the end cap 12 to isolate the electrical connection components in the housing 13 from the end cap 12 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0096] The shell 13 is a component used to cooperate with the end cap 12 to form the internal environment of the battery cell 10, wherein the formed internal environment can be used to accommodate the battery cell assembly 11, electrolyte and other components. The shell 13 and the end cap 12 can be independent components, and an opening can be set on the shell 13, and the internal environment of the battery cell 10 is formed by covering the opening with the end cap 12 at the opening. Without limitation, the end cap 12 and the shell 13 can also be integrated. Specifically, the end cap 12 and the shell 13 can form a common connection surface before other components are put into the shell, and when the interior of the shell 13 needs to be encapsulated, the end cap 12 covers the shell 13. The shell 13 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 13 can be determined according to the specific shape and size of the battery cell assembly 11. The material of the shell 13 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0097] The housing 13 may contain one or more battery cell assemblies 11. The portions of the positive and negative electrodes that do not contain active materials each constitute a tab 11a. The positive tab and the negative tab may be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 11a connects the electrode terminal to form a current loop.
[0098] Please refer to Figure 2 , Figure 2Schematic diagram of the exploded structure of the battery 100 provided for some embodiments of the present application. The battery 100 includes a box 20 and a battery cell 10, and the battery cell 10 is contained in the box 20. Among them, the box 20 is used to provide a storage space for the battery cell 10, and the box 20 can adopt a variety of structures. In some embodiments, the box 20 may include a first part 21 and a second part 22, the first part 21 and the second part 22 cover each other, and the first part 21 and the second part 22 jointly define a storage space for accommodating the battery cell 10. The second part 22 may be a hollow structure with one end open, the first part 21 may be a plate-like structure, and the first part 21 covers the open side of the second part 22, so that the first part 21 and the second part 22 jointly define a storage space; the first part 21 and the second part 22 may also be hollow structures with one side open, and the open side of the first part 21 covers the open side of the second part 22. Of course, the box 20 formed by the first part 21 and the second part 22 may be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0099] In the battery 100, there may be multiple battery cells 10, and the multiple battery cells 10 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 10 are both connected in series and in parallel. The multiple battery cells 10 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 10 is accommodated in the box 20; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 10 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 20. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 10.
[0100] The battery 100 in the embodiment of the present application includes a lithium-ion battery as a battery cell 10. In other embodiments, the battery 100 may further include any one or more of a lithium-sulfur battery, a sodium-ion battery, and a magnesium-ion battery, but is not limited thereto. The battery cell 10 may be cylindrical, flat, rectangular, or in other shapes.
[0101] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0102] In addition, the present application also provides an electrical device, which includes at least one of the battery cells and / or batteries provided in the present application. The battery cells or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0103] As an electric device, a battery cell and / or a battery 100 may be selected according to its usage requirements.
[0104] Figure 3a and Figure 3b As shown, it is an electric device as an example. The electric device is a vehicle such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. A structural schematic diagram of a vehicle 1000 is specifically provided. A battery 100 is arranged inside the vehicle 1000, and the battery 100 can be arranged at the bottom, head or tail of the vehicle 1000. The battery 100 can be used to power the vehicle 1000. For example, the battery 100 can be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to power the motor 300, for example, for the working power demand of the vehicle 1000 during starting, navigation and driving.
[0105] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0106] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0107] In the embodiments described below in this application, lithium difluorophosphate (LiPO 2 F 2 ), metal doping source (raw material containing T element), such as ZrO 2 、AlO 2 The dosages are all based on nickel-cobalt metal precursors.
[0108] Example 1
[0109] Preparation method of positive electrode active material:
[0110] (1)Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor was 1500ppm lithium difluorophosphate (LiPO 2 F 2 ), and dissolve it in water to obtain a difluorophosphate aqueous solution.
[0111] (2) In Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0112] (3) mixing the precursor coated with difluorophosphate with lithium carbonate at a molar ratio of 1:1.05; based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor, adding 1000ppm ZrO 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0113] Preparation method of positive electrode sheet:
[0114] The positive electrode active material 1, conductive carbon black (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N, N-dimethylpyrrolidone (NMP) in a weight ratio of 95.5:3:1.5, stirred evenly to obtain a slurry of the positive electrode sheet, and the slurry of the positive electrode sheet was evenly coated on both sides of the aluminum foil. The electrode sheet was cold pressed and sliced to obtain a positive electrode sheet.
[0115] Preparation method of negative electrode sheet:
[0116] Artificial graphite, nano-silicon, conductive carbon black (Super-P), carbon nanotubes, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR) are mixed with deionized water in a weight ratio of 95:5:0.5:0.1:1:1.5, and stirred evenly to obtain a slurry for coating the negative electrode sheet. The viscosity can be adjusted by deionized water during the stirring process. Then, the slurry is coated on both sides of the negative electrode collector with a certain width, and the negative electrode sheet is obtained by cold pressing and slicing. In the embodiment of the present application, the negative electrode collector is copper foil.
[0117] Preparation method of battery monomer:
[0118] The positive electrode sheet, the isolation film and the negative electrode sheet are wound into a battery cell assembly, and the battery cell is obtained through the electrode ear welding, aluminum shell packaging, liquid injection, packaging formation and vacuum molding. The width of the battery cell assembly is 148mm, the thickness is 28mm, the height is 98mm, and the capacity is 60Ah. Among them, the injected electrolyte is a 1mol / L LiPF6 solution, and the solvent of the LiPF6 solution is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 1:2. In the embodiment of the present application, the isolation membrane adopts 7μm thick polyethylene (PE).
[0119] Example 2
[0120] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0121] (1) Based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor was 4000ppm of lithium difluorophosphate (LiPO 2 F 2 ), and dissolve it in water until it is fully dissolved to obtain a difluorophosphate aqueous solution.
[0122] (2) In Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor is spray-coated with a 4000 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0123] (3) mixing the precursor coated with difluorophosphate with lithium carbonate at a molar ratio of 1:1.05; based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor, adding 1000ppm ZrO 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0124] Example 3
[0125] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0126] (1) Based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2The mass of the precursor was 1500ppm lithium difluorophosphate (LiPO 2 F 2 ), and dissolve it in water until it is fully dissolved to obtain a difluorophosphate aqueous solution.
[0127] (2) In Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0128] (3) mixing the precursor coated with difluorophosphate with lithium carbonate at a molar ratio of 1:1.05; based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor, adding 1000ppm AlO 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0129] Example 4
[0130] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0131] (1) Based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor was 1500ppm lithium difluorophosphate (LiPO 2 F 2 ), and dissolve it in water until it is fully dissolved to obtain a difluorophosphate aqueous solution.
[0132] (2) In Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0133] (3) mixing the precursor coated with difluorophosphate with lithium carbonate at a molar ratio of 1:1.05; based on Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The mass of the precursor, adding 1000ppm AlO 2 and 1000ppm ZrO 2, mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0134] Example 5
[0135] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0136] (1) 1500ppm lithium difluorophosphate (LiPO 2 F 2 ) is dissolved in water and fully dissolved to obtain a difluorophosphate aqueous solution.
[0137] (2) In Ni 0.65 Co 0.12 Mn 0.23 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 60 minutes.
[0138] (3) The precursor coated with difluorophosphate was mixed with lithium carbonate at a molar ratio of 1:1.05, and 1000 ppm ZrO 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0139] Example 6
[0140] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0141] (1) 300ppm lithium difluorophosphate (LiPO 2 F 2 ) is dissolved in water and fully dissolved to obtain a difluorophosphate aqueous solution.
[0142] (2) In Ni 0.65 Co 0.12 Mn 0.23 (OH) 2 The precursor is spray-coated with a 300 ppm aqueous solution of difluorophosphate, and the spraying time is 5 minutes.
[0143] (3) The precursor coated with difluorophosphate was mixed with lithium carbonate at a molar ratio of 1:1.05, and mixed in a high-speed mixer at a speed of 1500 rpm for 2 hours. The mixture was placed in a kiln and sintered at 950° C. for 10 hours, and then cooled to room temperature and crushed to obtain a positive electrode active material.
[0144] Example 7
[0145] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0146] (1) 1500ppm lithium difluorophosphate (LiPO 2 F 2 ) is dissolved in water and fully dissolved to obtain a difluorophosphate aqueous solution.
[0147] (2) In Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0148] (3) The precursor coated with difluorophosphate was mixed with lithium carbonate at a molar ratio of 1:1.05, and mixed in a high-speed mixer at a speed of 1500 rpm for 2 hours. The mixture was placed in a kiln and sintered at 930° C. for 33 hours, and then cooled to room temperature and crushed to obtain a positive electrode active material.
[0149] Example 8
[0150] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0151] (1) 1500ppm lithium difluorophosphate (LiPO 2 F 2 ) is dissolved in water and fully dissolved to obtain a difluorophosphate aqueous solution.
[0152] (2) In Ni 0.65 Co 0.12 Al 0.23 (OH) 2 The precursor is spray-coated with a 1500 ppm aqueous solution of difluorophosphate, and the spraying time is 20 minutes.
[0153] (3) The precursor coated with difluorophosphate was mixed with lithium carbonate at a molar ratio of 1:1.05, and 1000 ppm ZrO 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0154] Comparative Example 1
[0155] The difference from Example 1 lies in the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material of Comparative Example 1 is:
[0156] (1) Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor was mixed with lithium carbonate at a molar ratio of 1:1.05, mixed in a high-speed mixer at a speed of 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0157] Comparative Example 2
[0158] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0159] (1) Ni 0.65 Co 0.12 Mn 0.23 (OH) 2 The precursor was mixed with lithium carbonate at a molar ratio of 1:1.05, mixed in a high-speed mixer at a speed of 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0160] Comparative Example 3
[0161] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0162] (1) Ni 0.55 Co 0.06 Mn 0.39 (OH) 2 The precursor was mixed with lithium carbonate at a molar ratio of 1:1.05, and 1000 ppm ZrO was added. 2 , mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0163] Comparative Example 4
[0164] The difference from Example 1 is the preparation method of the positive electrode active material. Specifically, the preparation method of the positive electrode active material is:
[0165] (1) Ni 0.65 Co 012 Al 0.23 (OH) 2 The precursor was mixed with lithium carbonate at a molar ratio of 1:1.05, and 1000ppm ZrO 2, mixed in a high-speed mixer at 1500 rpm for 2 hours, sintered in a kiln at 900°C for 13 hours, cooled to room temperature and crushed to obtain the positive electrode active material.
[0166] The positive electrode active materials of the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 4 were made into corresponding batteries 1, 2, 3, 4, 5, 6, 7, 8 and batteries 9, 10, 11, 12, and the battery performance tests were carried out to obtain Table 1. Specifically, the battery high temperature gas generation test, gram capacity test, and high temperature storage performance test were carried out. The specific test conditions are:
[0167] 1. High temperature gas production test
[0168] The high temperature gas generation test method of the battery is to charge the battery to 4.5V at 1C and place it in a 70℃ constant temperature box for 30 days. The initial volume of the battery and the volume after 30 days of standing are measured by the drainage method to obtain the volume expansion rate of the battery. The volume expansion rate of the battery (%) = (volume after 30 days of standing / initial volume-1) × 100%.
[0169] 2. Battery gram capacity test
[0170] The battery capacity test is to place the battery at a constant temperature of 25°C for 2 hours, then charge it to 4.5V at 1 / 3C at 2.8V~4.5V, then charge it at a constant voltage at 4.5V to a current ≤0.05mA, place it at rest for 5 minutes, and then discharge it to 2.8V at 1C, and record the capacity C of the battery. 放 .
[0171] Gram capacity = battery capacity C 放 (mAh) / mass of positive electrode active material (g).
[0172] 3. High temperature storage performance test
[0173] At 25°C, the battery is charged to 4.5V at a constant current rate of 0.33C, then charged at a constant voltage until the current is less than or equal to 0.05C, and then discharged to 2.8V at a constant current rate of 0.33C, and the initial discharge capacity of the battery is obtained by testing. At 25°C, the battery is charged to 4.5V at a constant current rate of 0.33C, and then charged at a constant voltage until the current is less than or equal to 0.05C, and then the fully charged battery is placed in a 60°C oven. Take out the battery after high-temperature storage at an interval of 15 days, cool it naturally to 25°C, discharge it to 2.8V at a constant current rate of 0.33C, then charge it to 4.5V at a constant current rate of 0.33C, and then charge it at a constant voltage until the current is less than or equal to 0.05C, and then discharge it to 2.8V at a constant current rate of 0.33C, and the discharge capacity of the battery after 15 days of high-temperature storage is obtained by testing. Then put it in an oven at 60°C until the capacity retention rate is less than 80%. Repeat the test every 15 days.
[0174] Capacity retention rate of battery after 60 days of high temperature storage (%) = discharge capacity after 60 days of high temperature storage / initial discharge capacity × 100%. The number of days for the capacity to decay to 80% is obtained by drawing a line based on the test data.
[0175] 4. Volume average particle size Dv50 test.
[0176] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8% to 12% shading), add 20ml of deionized water, and ultrasonicate for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.
[0177]
[0178] Table 2 Process parameters and performance parameters of the embodiments and comparative examples
[0179]
[0180] As can be seen from the process parameters and performance parameters of Tables 1 and 2, based on Comparative Examples 1 to 4, the positive electrode active materials of Examples 1 to 8 of the present application are mixed with fluorine-phosphorus compounds in the positive electrode active main material, so that the high-temperature gas production performance of the positive electrode active materials of Examples 1 to 8 of the present application is significantly reduced to 20% to 43%, which is lower than 58% to 70% of Comparative Examples 1 to 4. The high-temperature storage performance of the positive electrode active materials of Examples 1 to 8 of the present application is significantly improved, and the high-temperature storage can reach 480 days to 650 days, which is much higher than 195 days to 210 days of Comparative Examples 1 to 4. The 1 / 3C capacity of the positive electrode active materials of Examples 1 to 8 of the present application is between 190 mAh / g and 198 mAh / g, and the positive electrode active materials of Examples 1 to 8 of the present application can also maintain a relatively high capacity. In Examples 1 to 8 of the present application, the positive electrode active main material includes a fluorine-phosphorus compound, and the fluorine-phosphorus compound includes lithium difluorophosphate. In embodiments 1 to 8 of the present application, a difluorophosphate solution is coated on the surface of a nickel-cobalt-manganese precursor or a nickel-cobalt-aluminum precursor by spraying, so that the fluorine-phosphorus compound in the positive active material is mixed with a high uniformity on the surface of the positive active main material, which is beneficial to improve the stability of the positive active main material. In the positive active main material of embodiments 1 to 8 of the present application, at a sintering temperature of 900°C to 950°C, the fluorine-phosphorus compound will decompose the F element and the P element to be doped into the bulk phase of the positive active main material, wherein the F element is doped into the oxygen position of the hexagonal system of the positive active main material, and the P element is doped into the hexagonal system lattice or / and the oxygen position of the hexagonal system of the positive active main material, thereby achieving the modification of the positive active main material, inhibiting the oxidation activity of the positive active main material, stabilizing the bulk structure of the positive active main material, and enhancing the stability of the positive active material under high temperature conditions, thereby significantly improving the storage performance and gas production problems of the battery.
[0181] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises: A positive electrode active main material, wherein the positive electrode active main material comprises lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide; A fluorine phosphorus compound is mixed in the positive electrode active host material.
2. The positive electrode active material according to claim 1, characterized in that The fluorine-phosphorus compound is located on the surface layer of the positive electrode active main material.
3. The positive electrode active material according to claim 1, characterized in that The fluorine phosphorus compound includes a structural formula of Li p P q O r The compound of F2, wherein 0.8≤p≤1.2, 0.8≤q≤1.2, and 1.8≤r≤2.
2.
4. The positive electrode active material according to claim 1 or 2, characterized in that: The positive electrode active main material includes a structural formula of Li(Ni x Co y M z ) 1-u T u O2 material, wherein M includes Mn or Al, T includes one or more of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al, x+y+z=1, 0.3≤x≤0.9, 0.03≤y≤0.3, 0.05≤z≤0.4, 0.0003≤u≤0.
004.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active main material is doped with fluorine and phosphorus elements.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The mass fraction of the fluorine-phosphorus compound to the total mass of the positive electrode active material is 0.015% to 0.4%.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The volume average particle size DV50 of the positive electrode active material is 3 μm to 15 μm.
8. A method for preparing a positive electrode active material, characterized in that: include: Spraying a difluorophosphate solution on a nickel-cobalt metal precursor so that the difluorophosphate is coated on the nickel-cobalt metal precursor, wherein the nickel-cobalt metal precursor includes a nickel-cobalt-manganese precursor or a nickel-cobalt-aluminum precursor; A nickel-cobalt metal precursor coated with difluorophosphate is mixed with a lithium source and sintered to form a lithium nickel-cobalt-manganese oxide or a lithium nickel-cobalt-aluminum oxide mixed with a fluorine-phosphorus compound.
9. The method for preparing a positive electrode active material according to claim 6, characterized in that: The spray coating spray time is 5 minutes to 60 minutes.
10. The method for preparing a positive electrode active material according to any one of claims 8 to 9, characterized in that: The mass ratio of the difluorophosphate in the difluorophosphate solution to the nickel-cobalt metal precursor is 3×10 -4 ~4×10 -3 :
1.
11. The method for preparing a positive electrode active material according to any one of claims 8 to 10, characterized in that: The method comprises mixing a nickel-cobalt metal precursor coated with difluorophosphate and a lithium source, comprising: Mixing a nickel-cobalt metal precursor coated with difluorophosphate, a lithium source and a metal doping source, wherein the metal doping source comprises one or more metal oxides of Zr, Sr, B, Ti, Mg, Na, Si, Sn, Tb, W, Nb, Sb and Al; Wherein, the nickel-cobalt metal precursor comprises a structural formula of (Ni a Co b M c ) d (OH)2, 0.3≤a≤0.9, 0.01≤b≤0.4, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, M includes Mn or Al; or / and, The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium acetate and lithium phosphate; or / and, The mixing speed is 600 rpm to 2000 rpm, and the mixing time is 30 min to 300 min.
12. The method for preparing a positive electrode active material according to any one of claims 8 to 11, characterized in that: The sintering temperature is 900° C. to 950° C., and the sintering time is 10 h to 33 h.
13. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 7, and / or the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 6 to 10.
14. A battery, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 8, and / or the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 6 to 10, or the positive electrode sheet according to claim 13.
15. An electrical equipment, characterized in that: Comprising the battery of claim 14.
Citation Information
Patent Citations
Nickel-cobalt-aluminum-lithium ion battery positive material as well as preparation method and application thereof
CN106654237A
Fluorine doping modified lithium ion battery rich-lithium positive electrode material and preparation method thereof
CN106784676A
Fluorine-phosphorus doped tin oxide coated modified positive pole material and preparation method thereof
CN110380043A
Positive electrode material as well as preparation method and application thereof
CN114784246A
A fluorine-phosphorus chaperone-doped ternary precursor, its preparation method, and ternary materials
CN114933336A